The Effect of CRM and Price Perception on Loyalty with Satisfaction as a Mediation Variable (A Study on Deposit Customers of PT. BPR BKK Blora (Perseroda) - Risma Setyani; Alimuddin Rizal Rivai (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
Customer loyalty is one of the foundations for assessing bank performance; loyal customers reflect loyalty to continue using bank products and services. In order to achieve customer loyalty, it is necessary to analyze several things, including customer relationship management, price perception, and customer satisfaction. The population used is PT BPR BKK Blora (Perseroda). The number of samples in this study includes 100 respondents taken using the Slovin formula. In this study, several tests were used, namely the description of respondents and variables, instrument tests on validity tests (KMO> 0.5 and component matrix> 0.4), and reliability tests (Cronbach alpha> 0.7), then in the regression test using the coefficient of determination test, F test (sig <0.05) and t test (sig <0.5). In the mediation test, the Sobel test was used (sig <0.05). Based on the results of the data analysis, a positive and significant influence was obtained between variables with a sig value <0.05 on: 1) CRM on satisfaction. 2) Price perception on satisfaction. 3) CRM on loyalty, 4) Price perception on loyalty, and 5) satisfaction on loyalty. The Sobel test also shows a similar result, with a sig value of <0.05, indicating that satisfaction mediates the influence of CRM and price perception on loyalty.